Clinical and dermoscopic features of congenital melanocytic nevi - Murat Orhan Oztas (Wolters Kluwer Medknow Publications, 2010)
Background: Congenital melanocytic nevi (CMN) are nevomelanocytic nevi which are present at birth. In this study, we set out to determine the clinical and dermoscopic properties of CMN. Methods: A total of 239 lesions were diagnosed as CMN. Dermoscopic properties were noted. Age, sex, nevus location and nevus size of the patients were also collected from the patient records. Results: A total of 239 lesions were diagnosed as CMN in 239 patients (age ranged from 1 month to 63 years (20.79 ± 13.76 yr); 114 [47.7%] males and 125 [52.3%] females). Most of the lesions were medium-sized CMN, followed by small and large ones. The most common localization was upper extremities (23.8%), followed by head and neck, back, and lower extremities respectively. Dark brown was the most common colour seen in dermoscopy (115 patients, 48.1%), followed by light brown (69 patients, 28.9%) and black (55 patients, 23%) respectively. The most common dermoscopic findings of CMN was hair follicles followed by dots (70%) and perifollicular hypopigmentation (51%). Conclusions: Our study describes the normal clinical and dermoscopic features of CMN. It should be kept in mind that, CMNs are quite common lesions, and melanomas can arise from them. Knowing and being familiar with the normal properties of these common nevi will help us determine whether a nevus is suspicious or not.